2011
DOI: 10.4021/gr356w
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori DNA in Liver Tissues From Chronic Hepatitis C Egyptian Patients

Abstract: BackgroundHepatitis C virus (HCV) is considered the most common etiology of chronic liver disease in Egypt, which may progress to cirrhosis and hepatocellular carcinoma (HCC). Previous studies have documented an association between Helicobacter pylori (H. pylori) infection and liver cirrhosis with or without HCC. This study aimed to investigate the presence of H. pylori DNA in the liver tissue of Egyptian patients with chronic hepatitis C (CHC).MethodsFifty-two CHC Egyptian patients were enrolled in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…These results are in partial agreement with a study conducted on 60 Egyptian HCV positive patients, their age ranged between 40 and 50 years TABLE 4 Comparison between the liver enzyme levels among the four studied groups using one-way analysis of variance (ANOVA) followed by post hoc analysis using the LSD test and 75% of them were males. 26 In the current study, the differences between the results of the biochemical tests of the control group and the HBV positive patients group were statistically insignificant except for the liver function tests, total bilirubin, ALT, AST, ALP, and GGT, which were found to be significantly higher in the patients group as a result of HBV infection and liver dysfunction.…”
Section: Discussioncontrasting
confidence: 44%
“…These results are in partial agreement with a study conducted on 60 Egyptian HCV positive patients, their age ranged between 40 and 50 years TABLE 4 Comparison between the liver enzyme levels among the four studied groups using one-way analysis of variance (ANOVA) followed by post hoc analysis using the LSD test and 75% of them were males. 26 In the current study, the differences between the results of the biochemical tests of the control group and the HBV positive patients group were statistically insignificant except for the liver function tests, total bilirubin, ALT, AST, ALP, and GGT, which were found to be significantly higher in the patients group as a result of HBV infection and liver dysfunction.…”
Section: Discussioncontrasting
confidence: 44%
“…H. pylori infection may also cause injuries in multiple organs, such as chronic injury of pancreas which affects liver function. etiologic agent which can also cause hepatocellular carcinoma and other liver complications and this finding corroborates the previously reported study that reported the presence of H. pylori in extra-hepatic tissues of human beings and mice [10].…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, liver cirrhosis at patient with concomitant H. pylori and chronic HCV infections showed a high percentage compared to those patients with chronic HCV mono-infection. Several previous reports revealed a strong association between H. pylori infection and the progression of liver injuries such as cirrhosis and fibrosis among HCV infected patients [28,34,35,37,38,40,41].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, in the current study, biochemical assessment and HCV RNA load at patient with concomitant H. pylori infection and chronic HCV infection was similar to patients with chronic HCV mono-infection. Several reports demonstrated that there was no statistical difference between ages, gender, liver function tests, AFP levels or viral load in the prevalence of H. pylori in HCV infected patients [37,40,41].…”
Section: Discussionmentioning
confidence: 99%